Automatic Room Temperature Regulator for Making Tempe Based on Arduino with Fuzzy Logic Method - and and (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2020)
The main obstacles of the tempe producers in fermentation process are the uncertain temperature and weather factors, if in the cold temperatures of tempe producers tend to still use manual way to keep the temperature in tempe, that is by covering the surface using cloth, newspaper or other cover because for the fermentation process in tempe temperature required ranges between 30-35o C and humidity below 70%. With unstable temperature can certainly affect the duration of tempe fermentation process. For that required a tool that can stabilize the temperature of the room on tempe fermentation process. Automatic temperature control for the manufacture of tempe is using fuzzy logic method as a smart control system, Arduino Mega 2560 as a microcontroller, DHT11 sensor as the detector temperature and humidity of the room, YL-69 & YL-38 sensors to detect the tempe water content that has become tempe parameter already mature or not, and heater and fan as actuators to stabilize the room temperature. Automatic temperature regulator for tempe making with fuzzy logic method is able to stabilize room temperature in fermentation process tempe and success rate of this tool in category good enough because get value from precision equal to 65%, recall 100%, and accuracy equal to 65%